The Analysis of the Problem Solving Ability of Middle School Students in Solving Circle Problems - Eko Saputra; Rino Rino; Andri Saputra (Education Mind Based Development Association, 2022)
This research is a type of descriptive qualitative research that aims to analyze the problem solving abilities of students. The data analyzed were in the form of problem solving ability test results. The abilities are analyzed based on 4 indicators, namely: understanding problems, planning problems, solving problems, and making conclusions. This test was conducted on February 28, 2022 at SMP Negeri 1 Paloh with a sample of 33 students of class VIII on the Circle material. Based on the results of the analysis, students have very low ability in solving problems. In the indicator of understanding the problem and making conclusions, many students did it wrong, even many did not write down the information and make conclusions. While on the indicators of making plans and solving problems, some students did not do it correctly.